The IASLC Lung Cancer Staging Project: Summary of Proposals for Revisions of the Classification of Lung Cancers with Multiple Pulmonary Sites of Involvement in the Forthcoming Eighth Edition of the TNM Classification. Issue 5 (May 2016) - Detterbeck, Frank C.; Nicholson, Andrew G.; Franklin, Wilbur A.; Marom, Edith M.; Travis, William D.; Girard, Nicolas; Arenberg, Douglas A.; Bolejack, Vanessa; Donington, Jessica S.; Mazzone, Peter J.; Tanoue, Lynn T.; Rusch, Valerie W.; et al.
ABSTRACT : Introduction: : Patients with lung cancer who harbor multiple pulmonary sites of disease have been challenging to classify; a subcommittee of the International Association for the Study of Lung Cancer Staging and Prognostic Factors Committee was charged with developing proposals for the eighth edition of the tumor, node, and metastasis (TNM) classification to address this issue. Methods: : A systematic literature review and analysis of the International Association for the Study of Lung Cancer database was performed to develop proposals for revision in an iterative process involving multispecialty international input and review. Results: : Details of the evidence base are summarized in other articles. Four patterns of disease are recognized; the clinical presentation, pathologic correlates, and biologic behavior of these suggest specific applications of the TNM classification rules. First, it is proposed that second primary lung cancers be designated with a T, N, and M category for each tumor. Second, tumors with a separate tumor nodule of the same histologic type (either suspected or proved) should be classified according to the location of the separate nodule relative to the index tumor—T3 for a same‐lobe, T4 for a same‐side (different lobe), and M1a for an other‐side location—with a single N and M category. Third, multiple tumors with prominent ground glass (imaging) or lepidic (histologic) features should be designated by the T category of the highest T lesion, the number or m in parentheses (#/m) to indicate the multiplicity, and a collective N and M category for all. Finally, it is proposed that diffuse pneumonic‐type lung cancers be designated by size (or T3) if in one lobe, T4 if involving multiple same‐side lobes, and M1a if involving both lungs with a single N and M category for all areas of involvement. Conclusion: : We propose to tailor TNM classification of multiple pulmonary sites of lung cancer to reflect the unique aspects of four different patterns of presentation. We hope that this will lead to more consistent classification and clarity in communication and facilitate further research in the nature and optimal treatment of these entities.